2017
DOI: 10.2147/ijgm.s135788
|View full text |Cite
|
Sign up to set email alerts
|

Inter-instrumental comparison for the measurement of electrolytes in patients admitted to the intensive care unit

Abstract: ObjectiveTo investigate whether benchtop auto-analyzers (AAs) and arterial blood gas (ABG) analyzers, for measuring electrolyte levels of patients admitted to intensive care units (ICU), are equal and whether they can be used interchangeably.Materials and methodThis study was conducted on 98 patients admitted to the ICU of the Institute of Medicine, Kathmandu, Nepal between 15 October and 15 December 2016. The sample for AA was collected from the peripheral vein through venipuncture, and that for ABG analyzer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…These results are generally in line with previously published data [15]. However, amongst other studies, Budak et al found out that even potassium test results obtained using an ABG and an AA differ and the data thus cannot be used interchangeably in clinical practice [20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are generally in line with previously published data [15]. However, amongst other studies, Budak et al found out that even potassium test results obtained using an ABG and an AA differ and the data thus cannot be used interchangeably in clinical practice [20].…”
Section: Discussionsupporting
confidence: 90%
“…These previously observed differences between the electrolyte levels measured using an AA and ABG analyzer may be explained on the basis of a combination of factors such as sample transport, dilution determinants, or instrument calibration. For instance, it is well known that ISE-based analysis devices from different manufacturers yield sodium/potassium levels that differ by 2–5% [15]. Moreover, for various types of heparin in blood gas syringes, a preanalytical bias in electrolyte concentrations was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitemia values from microscopy and from 18S qPCR showed good agreement and no evidence of systematic or proportional bias by Passing–Bablok regression, a method commonly used in clinical laboratory settings [14]. Our findings of a mean difference of 0.04 log 10 units/mL are supported by several smaller studies.…”
Section: Discussionsupporting
confidence: 79%
“…This may have been diminished or absent if the full range of potassium concentrations were evaluated. Previous studies that included samples across a wider range of potassium concentrations did not report any proportional systematic error ( 22 - 24 ).…”
Section: Discussionmentioning
confidence: 87%